?COMPLEXES OF Co (II), Ni (II), Cu (II), Zn (II), Cd ON-NO DONOR TETRADENTATE LIGAND (m AND Hg (m WITH (Biological Sciences - PJSIR, 1999)
Fifteen complexes of composition [MLX2] have been prepared where M=Co (II), Ni (II), Cu (II), Zn (II),.cd (II) and Hg (II); x=cr, NO-1, SCN-; L=1,9-dibenzoyl -2,8-di (p-methoxy phenyl) -3,7-diazanonane. The ligand possesses ON -NO donor atoms and forms mononuclear complex compounds with the above metal ions. The complexes have been characterised to be either octahedral or distorted octahedral basing upon conductance, magnetic susceptibility, IR, electronic, NMR and ESR spectra apart from x-ray diffraction data.